Comparative property law : global perspectives - Graziadei, Michele, 1958-; Smith, Lionel D., 1960- (Research handbooks in comparative law, 2017)
Comparative Property Law provides a comprehensive treatment of property law from a comparative and global perspective. The contributors are leading experts in their fields who cover both classic and new subjects, including the transfer of property, the public-private divide, water and forest laws and the property rights of aboriginal peoples. Incorporating contributions from a variety of countries, this Handbook explores property law with a critical edge, viewing the subject through the lens of both public and private law theory and providing a springboard for further research. This unique coverage of new and emerging subjects in property law also examines developments in Africa, Latin America and China. This Handbook maps the structure and the dynamics of property law in the contemporary world and will be an invaluable reference for scholars working across the breadth of the field.